An exploration of elite Japanese female footballers` acute cultural transition experiences in Europe - Hirose, K.; Meijen, C. (Science and Medicine in Football, 2022)
The globalisation of women`s football reflects the increasing number of female football players moving abroad for their professional careers. Yet, the cultural transition of Asian female athletes into western culture is merely studied. This study focused on the experiences of nine elite Japanese female football players competing in the professional league in Spain and Portugal in the immediate period after moving from Japan. During the semi-structured interview participants shared their experiences of their sporting and non-sporting lives abroad and the impact of this transition on their athletic and non-athletic self and well-being. By using thematic analysis three themes illustrating their positive acculturation experiences were identified: opening up to people`s kindness, redefining family, and learning a new mentality. Based on the concept of two types of happiness (interdependent and independent), and the collectivism versus individualism dichotomy, the influence of culture on the relationship between life satisfaction and athletic performance, personal growth, and expanding the support system were critically discussed. Practical implications include insights for sport professionals on how cultural change can affect transnational athletes` sporting and non-sporting lives and influence their mental health.